Wild and backyard food use during COVID-19 in upstate New York, United States - Coffin-Schmitt, Jeanne L.; Clements, Nia; Marshall, Grace; Liu, Lu; Trombitas, Aly; Wang, Zi; Yuan, Shuai; Safi, Amelia Greiner; Hanson, Karla L.; Fiorella, Kathryn J. (Frontiers in Nutrition, 2023)
COVID-19 acutely shocked both socio-economic and food systems in 2020. We investigated the impact of COVID-19 on production and consumption of gardened produce, backyard poultry, wild game and fish, and foraged mushrooms, berries, and other plants in New York State. We conducted an online, cross-sectional survey in October-December 2020 with a convenience sample of participants (n=505) with an interest in gardening, poultry rearing, foraging, hunting, and/or fishing from six counties in upstate New York. We recruited through the New York Department of Environmental Conservation, Cornell Cooperative Extension, and other relevant email and social media pages. Across the wild and backyard food production strategies, 4.0-14.3% of respondents reported engaging for the first time and 39.6-45.7% reported increased production (a little or a lot more), and 31.6-42.7% of respondents' production was the same as the previous year. Consumption of foods produced was widespread, including fruit and vegetables (97.6% of producers also consumed), backyard eggs (92.7%), and foraged foods (93.8%). For meats, a majority consumed backyard poultry meat (51.2%), wild-caught fish (69.7%), and wild game they hunted (80.1%). The frequency of consumption of fruit and vegetables (average of 13.5 times/month) and eggs (16.4 times/month) was very high, while average consumption of poultry meat, foraged foods, fish, and wild game ranged from 3.1 to 5.8 times/month. The number of respondents who reported "have more control over food availability" as motivation to produce all wild and backyard foods increased from 2019 to 2020 (p<0.05 -p<0.001). There was also a significant relationship between experiences of COVID-19 related hardship (i.e., food insecurity, income loss) with gardening and poultry-rearing (p≤0.05), but not with other production methods or with consumption of wild and backyard foods. Our findings help to locate the place of wild and backyard foods within COVID-19 impacted food environments, and describe food security as a particularly relevant motivation, among others, reported by respondents in 2020. Given this, New York State service providers can use these findings to tailor current future support for households exerting control over their own food